Many Phases in a Hairy Box in Three Dimensions - Shoichiro Miyashita (Universe)
In this paper, I investigate gravitational thermodynamics of the Einstein–Maxwell–scalar system in three dimensions without a cosmological constant. In a previous work by Krishnan, Shekhar, and Bala Subramanian, it was argued that this system has no BH saddles, but has only empty (flat space) saddles and boson star saddles. It was then concluded that the structure of the thermodynamic phase space is much simpler than in the higher-dimensional cases. I will show that, in addition to the known boson star and empty saddles, three more types of saddles exist in this system: the BG saddle, its hairy generalization, and a novel configuration called the boson star-PL saddle. As a result, the structure is richer than one might naively expect and is very similar to the higher-dimensional ones.